Magnetic excitations in frustrated fcc type-III antiferromagnet MnS2. (31st January 2019) - Chatterji, T; Regnault, L P; Ghosh, S; Singh, A
Abstract: Spin wave dispersion in the frustrated fcc type-III antiferromagnet MnS2 has been determined by inelastic neutron scattering using a triple-axis spectrometer. Existence of multiple spin wave branches, with significant separation between high-energy and low-energy modes highlighting the intrinsic magnetic frustration effect on the fcc lattice, is explained in terms of a spin wave analysis carried out for the antiferromagnetic Heisenberg model for this S = 5/2 system with nearest and next-nearest-neighbor exchange interactions. Comparison of the calculated dispersion with spin wave measurement also reveals small suppression of magnetic frustration resulting from reduced exchange interaction between frustrated spins, possibly arising from anisotropic deformation of the cubic structure.